2013
DOI: 10.1016/j.rtbm.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

European Rail Traffic Management System (ERTMS): Supporting competition on the European rail network?

Abstract: International audienceReform of the railway in Europe, which is based on a split between network and operating, is deeply linked with the improvements of the quality of service of the railway network. It is indeed clear that competition on the network will only work if network activities are reliable, fair und optimally priced. On this point rail operation in Europe remains connected through a fragmented network in which it was still difficult for the engines to cross national borders. Interoperability must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…58 It was created to replace the individual train control and command systems across Europe, providing interoperability for di®erent countries and manufacturers leading to an increase in the e±ciency of tra±c of both passenger and freight trains and the competitiveness of the European railway. 5,55,[59][60][61][62] The realization of interoperability is a precondition for other bene¯ts of ERTMS, such as improved tra±c management, optimized usage of energy and network resource, 63 enhanced pro¯tability, and customer service, with a contribution to overall environmental and energy e±ciency objectives. 59 Besides these, higher levels of safety for high-speed trains with only a few minutes headway between trains, ensured operational reliability and more tra±c within the same infrastructure À À À i.e., better capacity utilization, reduction of maintenance costs, 5,58,[63][64][65][66][67] and the creation of a common market of signaling equipment that also leads to reduction of costs, 58,59,65 are enabled.…”
Section: Description Of the Ertmsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 It was created to replace the individual train control and command systems across Europe, providing interoperability for di®erent countries and manufacturers leading to an increase in the e±ciency of tra±c of both passenger and freight trains and the competitiveness of the European railway. 5,55,[59][60][61][62] The realization of interoperability is a precondition for other bene¯ts of ERTMS, such as improved tra±c management, optimized usage of energy and network resource, 63 enhanced pro¯tability, and customer service, with a contribution to overall environmental and energy e±ciency objectives. 59 Besides these, higher levels of safety for high-speed trains with only a few minutes headway between trains, ensured operational reliability and more tra±c within the same infrastructure À À À i.e., better capacity utilization, reduction of maintenance costs, 5,58,[63][64][65][66][67] and the creation of a common market of signaling equipment that also leads to reduction of costs, 58,59,65 are enabled.…”
Section: Description Of the Ertmsmentioning
confidence: 99%
“…54,62 ETCS is composed of two modules (track and train) that allow data transmission in the cab from the signaling system and data processing by the board computer. 60 ETCS, based on the information about train speed, received from the trackside controls, in the case that maximum permitted speed is exceeded, slows the train automatically. 56 Other major subsystems of ERTMS are \European Vital Computer (EVC), an onboard computer for controlling and managing all the information; Eurobalise active and passive transponders, which lay in between the tracks and send information to the onboard balise transmission module (BTM); and Euroloop, an inductive loop based on a localized communication system for semi-continuous mode of communication".…”
Section: Ertms Is Composed Of Two Main Componentsmentioning
confidence: 99%
“…Nevertheless, some authors have shown that the European rail freight market still lags behind other modes, such as road or air, in terms of competitiveness (Guihery & Laroche, 2013;Bonnafous & Crozet, 2014;Gevaers et al, 2015). The same authors also question the impact that liberalisation and competition have had on market efficiency (Friebel et al, 2010).…”
Section: -A Long Path To Change In the Rail Freight Marketmentioning
confidence: 99%
“…Despite clear benefit from the implementation of ERTMS, progress has been reportedly slow and there are a number of technological, operational, human and costs factors to be addressed, before the full benefit of the implementation can be realized (Smith, Majumdar, & Ochieng, 2012). In addition, the challenge for successful innovation is to support the migration conditions from the old national networks, to the new system (Laroche & Guihéry, 2013). For a discussion of ERTMS vis-a-vis green corridors, please see Chap.…”
Section: Signalling Systems For Railmentioning
confidence: 99%